2019
DOI: 10.1080/13814788.2019.1580264
|View full text |Cite
|
Sign up to set email alerts
|

At what stage in the undergraduate curriculum is it best to train in family medicine? A study from two medical schools in Spain

Abstract: Background: A course in family medicine (FM) could dispel the possibility of negative stereotyping about this speciality, and instil in students a greater interest. However, when is it preferable: at the beginning or at the end of undergraduate training? Objectives: To determine changes in knowledge and attitudes towards FM by medical students completing a course in primary care at the beginning or the end of the undergraduate training and whether those changes anticipate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(13 reference statements)
0
1
0
1
Order By: Relevance
“…We have been questioning whether our GP course comes too late in our curriculum. However, Lopez-Garcia showed that at the end of undergraduate training, there are no significant differences between students who have taken a GP-course in the second year and those who took such a course in the sixth year regarding their postgraduate interest in general practice [20]. The fact that 71% of Ma3 students in this survey were interested in general practice probably helps explain the 30% enrolment by our graduate doctors in the postgraduate general practice training, while the average for the Netherlands is 22% [21].…”
Section: Comparison With Existing Literaturementioning
confidence: 98%
“…We have been questioning whether our GP course comes too late in our curriculum. However, Lopez-Garcia showed that at the end of undergraduate training, there are no significant differences between students who have taken a GP-course in the second year and those who took such a course in the sixth year regarding their postgraduate interest in general practice [20]. The fact that 71% of Ma3 students in this survey were interested in general practice probably helps explain the 30% enrolment by our graduate doctors in the postgraduate general practice training, while the average for the Netherlands is 22% [21].…”
Section: Comparison With Existing Literaturementioning
confidence: 98%
“…Apenas una décima parte lo consideran su primera opción laboral en cursos preclínicos 5 , y esa proporción disminuye al final del grado 6 . Las actitudes de las y los estudiantes hacia la Medicina Familiar son similares independientemente de que se imparta una asignatura específica en cursos clínicos o preclínicos, y no predicen la elección posterior de la especialidad 7 .…”
unclassified